Preventive use of beta-blockers for anthracycline-induced cardiotoxicity: A network meta-analysis - He, Dongsheng; Hu, Jun; Li, Ying; Zeng, Xiaofei (Frontiers in Cardiovascular Medicine, 2022)
Background Anthracyclines are commonly used chemotherapeutic agents to treat malignant tumors. However, cardiotoxicity is a potentially serious adverse effect of anthracyclines. Beta-blockers may be effective in preventing anthracycline-induced cardiotoxicity (AIC). However, the lack of direct comparisons of various beta-blockers interferes with clinical decision-making. Network meta-analysis (NMA) was performed to assess the effectiveness of beta-blockers for AIC. Methods We searched PubMed, Embase, Web of Science, and the Cochrane Central Register of Clinical Trials. The last update was in May 2022. Randomized controlled trials (RCT) of beta-blockers for AIC were included. Four beta-blockers were selected for comparison based on the number of studies. NMA was conducted with STATA 14.0 software. Results A total of 10 RCTs (875 patients) met the selection criteria. NMA results showed that carvedilol was superior to bisoprolol (SMD=-0.50, 95%CI (-0.91,-0.10)) and nebivolol (SMD=-1.46, 95%CI (-2.82,-0.11)) in a delay of LVEF. The results of the cumulative probability ordering are as follows: carvedilol (83.8%)>metoprolol (71.8%)>bisoprolol (43.9%)>placebo (40.9%) > nebivolol (9.5%). Conclusion Based on the available evidence, carvedilol is the best beta-blocker for AIC, followed by metoprolol. However, additional studies with large samples should be conducted to confirm our findings.